FOREIGN ELECTION INTERFERENCE AS A HYBRID THREAT TO NATIONAL SECURITY – PRESIDENTIAL ELECTIONS IN THE USA IN 2016 AND 2020 - Tadić, Dejan (Political Review, 2023)
The second decade of the twenty-first century was marked by an expansion of interest in hybrid threats to national security. Foreign election interference became actual during the 2016 US presidential elections. As one of the modalities of subversive activities, foreign election interference faced a practical transformation along with the development of new technologies and the expansion of the social networks’ influence. The hybrid character of foreign election interference is shown both in the fact that it can be realized in physical cyberspace by state or non-state actors. This hybrid threat is limited only by the imagination of its creators and the ability of its implementers. 2016 and 2020 United States presidential elections have shown that countries with the most complex security systems are not able to predict where the hybrid threat will realize. The author concludes that foreign election interference will remain actual in contemporary international relations, because of avoiding direct armed confrontation in gaining dominance in the interest zones of great and regional powers.